Bevacizumab in colorectal cancer: current and future directions. Issue 10 (October 2012) - Yeung, Yvonne; Tebbutt, Niall C
Bevacizumab is a humanized monoclonal antibody to VEGF-A, an important therapeutic target through its proangiogenic effects on a variety of tumors. Bevacizumab has demonstrated clinically meaningful benefit in conjunction with chemotherapy for patients with metastatic colorectal cancer as well as other tumor types. Bevacizumab is a well-tolerated therapy with regard to toxicity, in keeping with its biological vascular effect. In this era of personalized medicine, current Phase II and III trials are further defining its role at various stages of metastatic disease and the optimal sequencing with cytotoxic and other targeted agents to achieve further improvements in patient outcome. Translational research for biomarker discovery and validation and further study into mechanisms of resistance are essential for future development and sustained benefit with this class of therapeutic agents.